(untitled) (Research, Society and Development, 2021)
On January 30, 2020, the World Health Organization (WHO) declared the COVID-19 outbreak a public health emergency, and on March 11, the epidemic was updated to a pandemic. Without much ceremony, COVID-19 broke with our familiar routine, changing our daily lives. In this new scenario, uncertainties and insecurities were triggered or intensified. With the advancement of technology, the forms of perception and interaction with the world have changed and the crisis caused by the pandemic has brought with it a digital revolution, as social isolation has become an essential factor in combating the spread of the disease, with strict blocking rules and social distance in many countries. In view of this scenario, the objective of this study was to evaluate the quality of life of coffee growers in the COOPFAM cooperative in the city of Poço Fundo-MG through the SF-36 instrument via an online questionnaire during the COVID-19 pandemic. The SF-36 is a multidimensional questionnaire consisting of 36 items, encompassed in 8 scales or components: functional capacity, physical aspects, pain, general health, vitality, social aspects, emotional aspects, mental health and one more comparative evaluation question between current health conditions and that of a year ago. It assesses both the negative aspects of health (disease or illness) and the positive aspects (well-being).